2016
DOI: 10.1111/epi.13313
|View full text |Cite
|
Sign up to set email alerts
|

7TMRIin focal epilepsy with unrevealing conventional field strength imaging

Abstract: SUMMARYObjective: To assess the diagnostic yield of 7T magnetic resonance imaging (MRI) in detecting and characterizing structural lesions in patients with intractable focal epilepsy and unrevealing conventional (1.5 or 3T) MRI. Methods: We conducted an observational clinical imaging study on 21 patients (17 adults and 4 children) with intractable focal epilepsy, exhibiting clinical and electroencephalographic features consistent with a single seizure-onset zone (SOZ) and unrevealing conventional MRI. Patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
129
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(136 citation statements)
references
References 39 publications
6
129
0
1
Order By: Relevance
“…Paralleling increases in resolution, the use of quantitative MR contrasts may better separate intracortical myelin from iron compared to “weighted” contrasts, and thus add specificity to identify typical and atypical cortical laminar architecture. Preliminary assessments suggest benefits for localization . In TLE, a recent quantitative intracortical analysis—even at conventional 3T MRI—identified intracortical anomalies suggestive of myelin alterations in hippocampal allocortices and other temporolimbic areas, suggesting coupled microstructural perturbations in mesiotemporal and adjacent paralimbic networks …”
Section: Imaging the Lesion Spectrummentioning
confidence: 97%
“…Paralleling increases in resolution, the use of quantitative MR contrasts may better separate intracortical myelin from iron compared to “weighted” contrasts, and thus add specificity to identify typical and atypical cortical laminar architecture. Preliminary assessments suggest benefits for localization . In TLE, a recent quantitative intracortical analysis—even at conventional 3T MRI—identified intracortical anomalies suggestive of myelin alterations in hippocampal allocortices and other temporolimbic areas, suggesting coupled microstructural perturbations in mesiotemporal and adjacent paralimbic networks …”
Section: Imaging the Lesion Spectrummentioning
confidence: 97%
“…7) lends itself well to revealing cortical malformation in epilepsy. In one study where various contrasts (MPRAGE, GRE, IR-FSE, ) were recorded in patients with unlocalized dysplasias at lower field, it was found that a diagnostic gain in detection was obtained using GRE and FLAIR images (De Ciantis et al, 2016). In that study, four of the six patients with abnormal 7T findings underwent epilepsy surgery.…”
Section: Observation Of Small Dysplasias Cortical Malformation and Mmentioning
confidence: 99%
“…Even in those where imaging is normal, resection on the basis of an intracranial EEG abnormality is more likely to result in seizure freedom if the resected tissue is pathologically abnormal [173]. Increasing pre-operative identification of pathology through improved MRI, through higher field strengths up to 7 T in vivo and enhancing 3 T with automated measures of hippocampal volumes potentially gives a greater chance of identifying candidates who may benefit from surgery [174–176]. In those whom structural imaging remains negative, then FDG-PET can aid in the decision making, either in favour of surgery, e.g.…”
Section: Epilepsy Surgerymentioning
confidence: 99%